2016
DOI: 10.3748/wjg.v22.i40.8910
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and resistance mutations of hepatitis C virus on sequences in the European hepatitis C virus database

Abstract: AIMTo evaluate the occurrence of resistant mutations in treatment-naïve hepatitis C virus (HCV) sequences deposited in the European hepatitis C virus database (euHCVdb).METHODSThe sequences were downloaded from the euHCVdb (). The search was performed for full-length NS3 protease, NS5A and NS5B polymerase sequences of HCV, separated by genotypes 1a, 1b, 2a, 2b and 3a, and resulted in 798 NS3, 708 NS5A and 535 NS5B sequences from HCV genotypes 1a, 1b, 2a, 2b and 3a, after the exclusion of sequences containing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
(40 reference statements)
4
13
1
5
Order By: Relevance
“…In line with published data on the association between RAVs for different DAA and HCV genotype/subtype, this study indicated that subtype 1a and 1b presented RAVs especially for SMV and DSV, respectively, while RAVs for DCV, LDV and DSV were more represented in genotypes 3 and 4 [22,25].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In line with published data on the association between RAVs for different DAA and HCV genotype/subtype, this study indicated that subtype 1a and 1b presented RAVs especially for SMV and DSV, respectively, while RAVs for DCV, LDV and DSV were more represented in genotypes 3 and 4 [22,25].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with data on sequences from the European cohorts, NS5B RAVs were detected more frequently in subtype 1b (60%) compared to subtype 1a and genotype 4 (42%-32.5% and 25%, respectively) [31,25]. The substitution S556G, that confers intermediate resistance to DSV, appeared at a higher frequency in subtype 1b than in subtype 1a (56% vs. 28%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A naturally high rate of genetic mutation due to low fidelity of RNA replication generates genetic diversity of HCV (18). Based on genetic differences between HCV isolates, the HCV species is classified into six genotypes (1-6) with several subtypes within each genotype.…”
Section: Gene Structure and Genotypes Of Hcvmentioning
confidence: 99%